Analisis Kualitas Produk Terhadap Aplikasi Tokopedia Menggunakan Metode Kuantitatif - A. Faiz Ismail; Tata Sutabri (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2024)
The aim of this research is to analyze the influence of product quality offered through the Tokopedia application on consumer purchasing decisions. The method used is descriptive statistical analysis and linear regression testing with a quantitative approach. The research sample consisted of 110 respondents from active Tokopedia users, whose data was collected through an online survey. The research results show that product quality has a positive and significant effect on purchasing decisions. The average product quality score of respondents was 4.16, which shows consumer satisfaction with the products available. Factors such as durability, noise, and conformity to specifications are important indicators for exuding product quality. This research also shows that the features in the Tokopedia application help improve consumer perceptions of product quality. Therefore, in order for Tokopedia to remain competitive in the e-commerce market, its main focus is developing application functionality and improving product quality